PERHITUNGAN HARGA POKOK PRODUKSI (FULL COSTING) SEBAGAI DASAR PENETAPAN HARGA JUAL PADA PABRIK KERIPIK TEMPE IBU NOVI DI KELURAHAN GUNUNG SAMARINDA BARU - Prihanisetyo, Adi (STIE Madani Balikpapan, 2025)
Calculation of Cost of Goods Manufactured (COGM) is the most important part needed by company management to determine the selling price of a product. To determine the right selling price, the company must first know the COGM of the product to be sold. The company's production results are influenced by the procurement of raw materials, labor, and factory overhead costs. This research aims to understand how to manage financial data from